The wandering hill - McMurtry, Larry (McMurtry, Larry. Berrybender narratives, 2005)
McMurtry continues the story of Tasmin Berrybender and her family in the unexplored Wild West of the 1830s, at that point in time when Lewis and Clark are still a living memory, and when the clash between the powerful Indian tribes of the Missouri and the encroaching white Americans is about to turn into full-blown tragedy.